Hubungan Pengetahuan dan Sikap Ibu Hamil dengan Kepatuhan Konsumsi Tablet Tambah Darah di Wilayah Kerja UPTD Puskesmas Semulajadi Kecamatan Datuk Bandar Timur Kota Tanjung Balai Tahun 2023 - Ariska Fauzianty; Nova Isabella Mariance Br Napitupulu; Emi Sriyanti Wijaya (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Anemia during pregnancy is still a global problem throughout the world. One of the causes of the high rate of anemia is non-compliance. Many factors influence the occurrence of compliance with the consumption of Fe tablets, namely attitudes and knowledge. To determine the relationship between knowledge and attitudes of pregnant women with compliance with the consumption of iron tablets in the work area of ​​the Semula Jadi Health Center UPTD, Datuk Bandar Timur District, Tanjung Balai City in 2023. This study used a descriptive correlation design with a cross-sectional approach. Data analysis used the Chi Square test method. This study was conducted in the work area of ​​the Semula Jadi Health Center with 34 people. Most of the respondents had less knowledge, as many as 22 respondents (51.2%), had a positive attitude, as many as 15 respondents (65.1%), and most of the respondents were not compliant with consuming iron tablets, as many as 24 respondents (55.8%). There is a significant relationship between maternal knowledge and compliance with the consumption of iron tablets with a p value <0.05 (0.012). There is a significant relationship between maternal attitudes and compliance with the consumption of iron tablets with a p value <0.05 (0.019). Midwives are expected to emphasize more on counseling related to how to consume iron tablets, especially drinks that can block iron absorption, risk factors for anemia, causes of anemia and treatment of anemia during pregnancy.